Risk factors for admission at three urban emergency departments in England: a cross-sectional analysis of attendances over 1 month. Issue 6 (22nd June 2017) - Ismail, Sharif A; Pope, Ian; Bloom, Benjamin; Catalao, Raquel; Green, Emilie; Longbottom, Rebecca E; Jansen, Gwyneth; McCoy, David; Harris, Tim
Abstract : Objective: To investigate factors associated with unscheduled admission following presentation to emergency departments (EDs) at three hospitals in England. Design and setting: Cross-sectional analysis of attendance data for patients from three urban EDs in England: a large teaching hospital and major trauma centre (site 1) and two district general hospitals (sites 2 and 3). Variables included patient age, gender, ethnicity, deprivation score, arrival date and time, arrival by ambulance or otherwise, a variety of ED workload measures, inpatient bed occupancy rates and admission outcome. Coding inconsistencies in routine ED data used for this study meant that diagnosis could not be included. Outcome measure: The primary outcome for the study was unscheduled admission. Participants: All adults aged 16 and older attending the three inner London EDs in December 2013. Data on 19 734 unique patient attendances were gathered. Results: Outcome data were available for 19 721 attendances (>99%), of whom 6263 (32%) were admitted to hospital. Site 1 was set as the baseline site for analysis of admission risk. Risk of admission was significantly greater at sites 2 and 3 (adjusted OR (AOR) relative to site 1 for site 2 was 1.89, 95% CI 1.74 to 2.05, p<0.001) and for patients of black or black British ethnicity (AOR 1.29, 1.16 to 1.44, p<0.001). Deprivation was strongly associated with admission. Analysis of departmental and hospital-wide workload pressures gave conflicting results, but proximity to the "4-hour target" (a rule that limits patient stays in EDs to 4 hours in the National Health Service in England) emerged as a strong driver for admission in this analysis (AOR 3.61, 95% CI 3.30 to 3.95, p<0.001). Conclusion: This study found statistically significant variations in odds of admission between hospital sites when adjusting for various patient demographic and presentation factors, suggesting important variations in ED-level and clinician-level behaviour relating to admission decisions. The 4-hour target is a strong driver for emergency admission.